ChemInform Abstract: Enantioselective Synthesis of N‐PMP‐1, 2‐Dihydropyridines via Formal [4 + 2] Cycloaddition Between Aqueous Glutaraldehyde and Imines. Issue 13 (March 2016) - Ramaraju, Panduga; Mir, Nisar A.; Singh, Deepika; Gupta, Vivek K.; Kant, Rajni; Kumar, Indresh
Abstract: The two‐step, one‐pot procedure involves an amino‐catalytic direct Mannich reaction/cyclization sequence followed by an IBX‐mediated chemo‐ and regioselective oxidation.